2018
DOI: 10.1186/s12985-018-1022-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antiviral activity of twenty-seven medicinal plant extracts from Southwest Nigeria against three serotypes of echoviruses

Abstract: BackgroundEchoviruses, a serotype of enteroviruses, infect millions of people globally and there is no specific drug treatment or vaccine available for its management. The screening of medicinal plants used locally for the treatment of infectious diseases, can provide a reliable option in the discovery of potent therapeutic compounds. This study was carried out to investigate the antiviral activities of 27 medicinal plant extracts, belonging to 26 different plant species, selected from Nigerian ethnobotany, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 42 publications
0
63
0
1
Order By: Relevance
“…In fact, 9 displayed SI value that is similar to that of vinblastine, indicating that it is only two to three times more cytotoxic to the cancer cells than the PNT2 cells. Recent studies have revealed the promising antibacterial, antifungal, antiprotozoal and antiviral activities of the extract of the leaves of M. barteri, and stated that at the tested doses, the extract could be considered relatively safe and non-toxic [40][41][42]. The antiproliferative activity of the DCM fraction of M. barteri reported herein and the abundance of cytotoxic compounds in this plant may provide evidence for its use in folklore medicine for the treatment of various cancers.…”
Section: Resultsmentioning
confidence: 60%
“…In fact, 9 displayed SI value that is similar to that of vinblastine, indicating that it is only two to three times more cytotoxic to the cancer cells than the PNT2 cells. Recent studies have revealed the promising antibacterial, antifungal, antiprotozoal and antiviral activities of the extract of the leaves of M. barteri, and stated that at the tested doses, the extract could be considered relatively safe and non-toxic [40][41][42]. The antiproliferative activity of the DCM fraction of M. barteri reported herein and the abundance of cytotoxic compounds in this plant may provide evidence for its use in folklore medicine for the treatment of various cancers.…”
Section: Resultsmentioning
confidence: 60%
“…Medicinal plants are a good source of potent and safe natural extracts that could act as adjuvants or even be an alternative to costly antibiotics against which microbes are becoming resistant day by day. Moreover, these extracts are cost-effective and work effectively against a variety of microbes, including bacteria, fungus, and viruses [ 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Medicinal plants have wide patronage due to their accessibility, potency and affordability. There have been several reports of successful treatment of various disease conditions with herbal therapy (28)(29)(30)(31). In the present study, 77 medicinal plants belonging to76 genera in 44 plant families were used by the respondents in the management of DM and its co-morbidities.…”
Section: Diversity Of Medicinal Plants Herbal Preparation and Adminimentioning
confidence: 95%